Mechanism of pulsatile flushing technique for saline injection via a peripheral intravenous catheter. (December 2020) - Zhu, Lei; Liu, Haibo; Wang, Rui; Yu, Yingqing; Zheng, Fuhong; Yin, Jianmei
Abstract: Background: The underlying mechanism of pulsatile flushing technique has not been fully elucidated, and the partial understanding of the mechanism has been confined to hydrodynamic simulation, ignoring the dynamic interaction among the catheter, blood vessel, blood stream, and saline. Methods: The peripheral intravenous catheter and vein models and their internal flow fields were assessed using a commercial software. The parameters of both fluid and structural mechanics were calculated and compared in the push and pause phase. The effect of different flushing volumes per bolus before each pause (0.5, 1.0, 1.5, and 2.0 mL) were compared, respectively corresponding to group (A, B, C and D). Findings: In groups C and D, the wall shear stress value (≥2 Pa) and enhanced shear rates (peaks up to 10, 000 s −1 ) were higher in the vessel wall near the catheter tip, which may be at risk of vascular endothelial injury. Furthermore, extraluminal flushing might be attributed to the recirculation of jet from the catheter outlet. The vortices of all groups faded away in an extremely short period (≤0.1 s) if the push was suddenly discontinued. Finally, overlarge displacement of the catheter tip in groups C and D (0.91 and 1.1 mm, respectively) caused the peripheral intravenous catheters to angle with the venous wall. Interpretation: The pulsatile flushing technique can facilitate intra- and extraluminal flushing of peripheral intravenous catheters. Furthermore, an insufficient volume per bolus can lead to inefficient flushing, and an overdose of single push may cause mechanical endothelial injury. Highlights: Extraluminal flushing mechanisms were observed in the pulsatile flushing. Pulsatile flushing of peripheral venous catheter doesn't rely on timing interval. Powerful injection will lead to a traumatic movement of the catheter tip.